2015
DOI: 10.1016/j.ejmp.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric-modulated arc therapy for oropharyngeal carcinoma: A dosimetric and delivery efficiency comparison with static-field IMRT

Abstract: The purpose of this study is to evaluate the treatment plan adequacy and delivery efficiency among volumetric-modulated arc therapy (VMAT) with one or two arcs and the conventional static-field dynamic multileaf collimator (dMLC) intensity-modulated radiation therapy (IMRT) in patients undergoing oropharyngeal carcinoma. Fifteen patient cases were included in this investigation. Each of the cases was planned using step-and-shoot IMRT, VMAT with a single arc (Arc1) and VMAT with double arcs (Arc2). A two-dose l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 20 publications
1
14
0
9
Order By: Relevance
“…The use of one-arc VMAT may shorten the delivery time further; however, in our preliminary evaluation, we found that the dose distribution of one-arc VMAT was inferior to that of twoarc VMAT. This finding was consistent with that of Dai et al 28 who found the dosimetric benefit of two-arc VMAT over one arc for the treatment of head and neck cancer. Therefore, we used two-arc VMAT for this study.…”
Section: Discussionsupporting
confidence: 92%
“…The use of one-arc VMAT may shorten the delivery time further; however, in our preliminary evaluation, we found that the dose distribution of one-arc VMAT was inferior to that of twoarc VMAT. This finding was consistent with that of Dai et al 28 who found the dosimetric benefit of two-arc VMAT over one arc for the treatment of head and neck cancer. Therefore, we used two-arc VMAT for this study.…”
Section: Discussionsupporting
confidence: 92%
“…Most previous dosimetric studies reported that VMAT plans provide no worse OAR sparing than SS‐IMRT . Only a few studies demonstrated significantly better OAR sparing in treating OPSCC with VMAT compared to SS‐IMRT.…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study were highlighted in red or pink. Note that different definitions of D max were used for brainstem and spinal cord among the publications (Bertelsen et al, Doornaert et al, Holt et al, and Pursley et al: D max ; Franzese et al and Vanetti et al: D 2% ; Scorsetti et al: D 1% ; Johnston et al: D 1cc ; Clemente et al, Dai et al, and Huang et al: D 0.1cc ). Abbreviations: Cord, spinal cord; OC, oral cavity; PC, pharyngeal constrictors; PG, parotid gland; C/I/L/RPG = contralateral/ipsilateral/left/right parotid gland; SMG, submandibular gland; C/I/L/RSMG, contralateral/ipsilateral/left/right submandibular gland [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Discussionmentioning
confidence: 99%
“…VMAT provides dose distributions that are comparable or superior to those of conventional intensity modulated radiation therapy, with a shorter treatment time. [1][2][3] The VMAT technique is especially beneficial for patients with head and neck cancer because in most cases the tumor is adjacent to critical organs. In these complex regions, a smaller margin size is desirable to minimize radiation-related toxicities.…”
Section: Introductionmentioning
confidence: 99%